Structural and photoluminescence properties of nanostructured zinc oxide synthesized by immersion method / Azlinda Ab. Aziz - Ab. Aziz, Azlinda (2016)
In this present work, Zinc oxide (ZnO) nanostructures on gold-coated silicon (Si) substrate were prepared from zinc nitrate hexahydrate (Zn(N03)2.6HO) and urea (CH4N2O) using a low-temperature solution-immersion method. High hierarchical structure of ZnO with high surface area were successfully synthesised by the immersion method through optimization of the reaction parameters, such as different substrate surface, alignment of substrate, concentration of precursor, ratio of stabiliser in solution, and different heat temperature. FESEM, EDX, XRD, AFM and PL were the selected characterization tools to analyse the morphological, structural, surface analysis and optical properties of ZnO nanostructures. FESEM images revealed that ZnO flowerlike microspheres consist of nanosheets was the dominant structure growth along synthesis parameter. The results give evidence that the smallest diameter -11-13 |um of ZnO micro-flowers was successfully formed on gold-coated Si substrate, and gold served as a nucleation sites for the growth of ZnO micro-flowers. Low average surface roughness of ZnO nanostructures had shown the uniformity of particles size on gold-coated Si surface. The alignment of substrate tilt towards 60 ° was the better alignment towards smallest crystallite size 28.5 nm. PL emission spectra of ZnO nanostructures consistently produced UV (398-416 nm) and visible emissions (450- 750 nm). UV peak corresponds to the ZnO nanostructures while peak at visible range relates to ZnO defects. PL results indicated that 0.40 M concentration of zinc nitrate and urea at 1:1 ratio had successfully formed ZnO micro-flowers consist of nanostructures with high intensity of UV emission, confirming high optical properties of the samples. At 500 °C of thermal treatment, ZnO nanostructures gave extremely high PL intensity which improved its optical property with better crystallization. Furthermore, additional analysis by PL temperature dependence of ZnO nanostructures sample had shown that the emission energies and intensities of the ZnO nanostructured strongly affected by the applied temperature. A plausible mechanism of the dissociation-deposition formation of micro-flower assembly of ZnO nanosheets from Zn(N03)2 and urea solution was also proposed.